Hydrothermal growth of MoSe2 nanoflowers for photo- and humidity sensor applications - Shelke, Nitin T.; Late, Dattatray J. (Sensors and Actuators A-Physical, 2019)
In the present investigation, we report the synthesis of molybdenum diselenide (MoSe2) nanoflowers by facile hydrothermal method for photo- and humidity sensor applications. The obtained samples were characterized thoroughly by x-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The XRD spectrum shows crystalline nature of the sample. Raman spectroscopy shows two prominent vibration modes of E-2 (g)1 and A(1g) at (2) over tilde 41 and (2) over tilde 83 cm(-1) respectively. The crystalline nature of the sample confirmed with the TEM. The MoSe2 nanoflowers based sensor shows high photosensitivity and good response to humidity with excellent prolong stability. The maximum photoresponsitivity of (1) over tilde 94% along with response of (4) over tilde0 ms and recovery time of (4) over tilde8 ms were observed for the sample. In case of humidity sensor, response time of (5) over tilde3 s and recovery time of (1) over tilde3 s with maximum sensitivity -74% were observed under humidity environments. It suggests that, MoSe2 nanoflowers appear as a potential candidate for constructing high-performance nanoelectronics devices. (C) 2019 Elsevier B.V. All rights reserved.